(Methods of analysis of urban and domestic consumption of water in the city of Erbil and assessment of future need) - Safar, Zine El Abidine Ali; Jameel, Samir Hamou (Journal of natural sciences, life and applied sciences, 2018)
Water is the most important resource that directly affects the different economic, social and urban development of its money.It plays a major role in the development, progress and stability of societies in any city or region Hence the importance of this study, which dealt with the analysis of the aspects of domestic water consumption in Erbil city and appreciation of the future need of the city’s residents according to local and international planning standards that provide the basic needs of this vital resource which cannot be dispensed with.The study examined the field survey and analysis of the results of the methods of consumption of water by the static households in the city, and factors affecting the variation in the rates of consumption of domestic water, and estimated the rate of consumption per day per capita of 377 liters/ person/ day.